Androgenetic alopecia: An updateCapsule Summary - Sincengile Ntshingila, PhD; Ogheneochuko Oputu, PhD; Afolake T. Arowolo, PhD; Nonhlanhla P. Khumalo, FCDerm, PhD (Elsevier, 2023)
Androgenetic alopecia (AGA) is the most common nonscarring alopecia and is characterised by distinct gradual patterned hair loss. AGA is mediated by genetic predisposition and excessive follicular sensitivity to androgens, mainly in males, leading to the progressive conversion of scalp terminal hair into vellus hair. Although highly prevalent, it is not fatal but may have a severe psychosocial impact, especially on females and younger males. Significant advances have been made in understanding AGA's epidemiology and pathophysiology, but only 2 drugs remain approved by the FDA - finasteride and minoxidil. Prolonged use of these drugs, is a prerequisite for enhanced treatment response. However, this leads to poor medication adherence and adverse effects from extended use eg, the "postfinasteride syndrome" which persists beyond stopping the drug. Hence, there is a need for research on more effective alternative treatments for AGA, with fewer side effects.This paper reviewed recent advances in AGA pathophysiology and its treatment options. The recently characterized structure of type 2, 5-alpha reductase holds significance in comprehending present and prospective treatments of AGA.